Research on The Coordination Mechanism of Tax Collection and Management Between China and ASEAN Countries under The Background of Digital Economy - Zhiming Wu; Liang Lv; Chang-sheng Tang (International Journal of Management and Education in Human Development, 2022)
With the rapid development of economic globalization, regional economic integration has become an important trend in the process of world economic development. The formal signing of the regional comprehensive economic partnership agreement (RCEP) marks a closer trade and investment exchanges between China and ASEAN. At the same time, the epidemic has given birth to the development of new industries and new formats. China and ASEAN have accelerated their exploration of digital transformation and development. Digital economic cooperation has become a new highlight of China ASEAN cooperation. Digital economic cooperation has gradually become an important field of cooperat ion between China and ASEAN countries. As an important part of modern economic system, digital economy not only profoundly changes the international economic form, but also brings many challenges to cross-border tax collection and management. Therefore, in the context of digital economy, how to eliminate regional tax barriers and reasonably distribute tax interests among countries in the region has become the core content of international tax coordination and jurisdiction among ASEAN countries. Deepening the research on tax coordination and jurisdiction of digital economy in China ASEAN free trade area is not only an important content and requirement of the construction of China ASEAN Free Trade Area, but also of great significance to promote the construction of China ASEAN Free Trade Area and promote regional economic prosperity and stability.